ANALYSIS OF USER SATISFACTION WITH THE VERONIKA DIGITAL CHATBOT SERVICE ON THE MY TELKOMSEL APPLICATION - Lareh, Dang Tuanku; Sholikhah, Sholikhah; Krissanya , Nofriska (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
This research aims to analyze user satisfaction with Veronika's digital chatbot service in the MyTelkomsel application using the Delone and McLean information system model as a theoretical framework. This research focuses on the population of MyTelkomsel application users who have experience using the Veronika chatbot. This research uses a survey method to collect data from a sample of users. The data obtained will be analyzed to identify factors that influence user satisfaction, which include system quality, information quality and service quality, user intensity, user satisfaction and impact of use. It is hoped that the results of this research will provide in-depth insight into the effectiveness of Veronika's chatbot services as well as recommendations for improving the quality of digital services in the future.